Comparative Effectiveness of Channa micropeltes Albumin Extract Versus Human Albumin on Lactate and Central Venous Oxygen Saturation as Predictors of Mortality in Critically Ill Patients with Hypoalbuminemia: A Double-Blind Randomized Controlled Trial - Purwoko; Bambang Novianto Putro; Juliana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Hypoalbuminemia is highly prevalent in critically ill patients and is linked to impaired tissue perfusion and increased mortality. Human albumin is the gold-standard replacement but is costly and largely imported. Channa micropeltes (giant snakehead) albumin extract is a potential economical local alternative, yet comparative evidence on tissue-perfusion biomarkers—lactate and central venous oxygen saturation (ScvO2)—as predictors of mortality is scarce. Methods: A double-blind randomized controlled trial in the intensive care unit of Dr. Moewardi Regional General Hospital, Surakarta, enrolled 32 adults with serum albumin <2.8 g/dL randomized to oral Channa micropeltes extract 5 g every 12 h (n=16) or intravenous 20% human albumin (n=16) for three days. Lactate and ScvO2 were sampled via central venous catheter on day 0 and day 3; mortality was followed to day 4. Analyses included repeated-measures ANOVA, Cohen's d, ROC curves and multivariable logistic regression. Results: Lactate fell in both arms (Channa 5.29±1.32 to 3.52±1.00; human 5.31±0.94 to 3.63±1.09 mmol/L; both p<0.001; d≥1.5) and ScvO2 rose (Channa +10.53%; human +9.54%; both p<0.001), with no between-group difference (Δ lactate p=0.812; Δ ScvO2 p=0.620). Day-3 biomarker AUCs for mortality were 0.572 and 0.498. Albumin type was not associated with mortality (adjusted OR 0.354; 95% CI 0.067–1.862; p=0.220; NNT 16). No serious adverse events occurred. Conclusion: Channa micropeltes albumin extract was non-inferior to human albumin for restoring tissue-perfusion biomarkers, supporting its potential as an economical, locally available alternative in critically ill patients with hypoalbuminemia.